Dynamic analysis of a human-transporting robot climbing stairs - Dat, Duong Tan; Ky, Le Hong; Thuan, Tran Duc (International Journal of Electrical and Computer Engineering (IJECE), 2026)
Robots used for transporting people on stairs face several limitations regarding tipping and safety hazards. Changes in the robot's center of gravity during stair climbing can generate tipping moments, leading to instability, tipping, and increased danger to users. This paper presents the modeling and analysis results of a tracked robot for transporting people on stairs, equipped with an anti-tipping mechanism based on center of gravity balance, combined with a vibration-damping mechanism mounted at the rear of the robot to enhance stability during stair climbing. Based on Newton-Euler's formulas, robot dynamics equations are established to describe the motion and analyze the robot's stability characteristics. Simulation and experimental results investigating the changes in center of gravity, velocity, tipping moment, and balancing moment of the robot during uphill and downhill movement were performed using MATLAB Simulink software. Simulation results indicate that the robot's center of gravity is adjusted and stabilized throughout both uphill and downhill movements. Practical experiments conducted on a fabricated robot model, capable of carrying a 100 kg load and moving up and down stairs with a 35-degree incline, demonstrated the feasibility and effectiveness of the proposed mechanical design. The results showed good agreement in kinematic trends between experimental and simulated data during the stair climbing, stair-on, and stair-step transition phases. This agreement between experimental and simulation results proved the correctness of the robot system and the constructed dynamic model. The research results provide a basis for developing control algorithms for robots that efficiently transport people up and down stairs in buildings.